2021
DOI: 10.1029/2020wr029361
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Methods and Imaging for Enzymatically Induced Calcite Precipitation in a Microfluidic Cell

Abstract:  4 NH) and bicarbonate are the dominant products of hydrolysis, see Equation 1 (Mitchell et al., 2019). However, carbon dioxide in aqueous solutions occurs as carbonic acid (H 2 CO 3), bicarbonate ( 3 HCO), or carbonate ( 2 3 CO), depending on the pH value. Since ammonia acts as a weak base by taking up a proton and producing hydroxide, it increases the pH value and shifts the equilibrium toward carbonate ions. The additional presence of calcium ions, in our case provided by adding calcium chloride, forces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Traditionally, biocemented samples are observed through scanning electron microscopy (SEM), which requires destructive, posttreatment sampling to provide detailed qualitative information about the fabric and texture of the biocemented soils 23 . In recent years, experimental setups that combine microfluidics and imaging have been developed to probe microscale processes of MICP [23][24][25][26][27][28][29] and Enzymatically Induced Calcite Precipitation (EICP) 30,31 in real-time. Microfluidic devices integrate porous networks (known as a lab-on-a-chip) and facilitate imaging and tracking.…”
Section: Microfluidic Study In a Meter-long Reactive Path Reveals How...mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, biocemented samples are observed through scanning electron microscopy (SEM), which requires destructive, posttreatment sampling to provide detailed qualitative information about the fabric and texture of the biocemented soils 23 . In recent years, experimental setups that combine microfluidics and imaging have been developed to probe microscale processes of MICP [23][24][25][26][27][28][29] and Enzymatically Induced Calcite Precipitation (EICP) 30,31 in real-time. Microfluidic devices integrate porous networks (known as a lab-on-a-chip) and facilitate imaging and tracking.…”
Section: Microfluidic Study In a Meter-long Reactive Path Reveals How...mentioning
confidence: 99%
“…Since microfluidics enables only 2D imaging, assumptions had to be made regarding the shape of the crystals (spherical and semispherical) to evaluate the crystal growth in three dimensions. Weinhardt et al 31 , 37 presented an experimental setup for the robust measurement of pressure in PDMS microfluidic channels of quasi 1D and quasi 2D pore structure geometries and few mm length during CaCO 3 precipitation via EICP and observed the influence of the geometry on porosity–permeability relationship. Using X-ray microcomputed tomography (XRCT), which resolves the third dimension of the CaCO 3 precipitates after the end of the EICP treatment, suggested that the spheroidal and frustum shapes can be used to calculate the volume of precipitated CaCO 3 from 2D projections.…”
Section: Introductionmentioning
confidence: 99%
“…Transport or hydrochemical induced clogging indicate that numerical permeability results tend to be too high compared to laboratory measurements (Figure 3D). In this respect, we recommend explicit investigations of particle transport or mineral scaling in the Ruhr sandstone based on XRCT and other imaging techniques (e.g, Weinhardt et al, 2021). Until then, the segmented soiled pore phase provides an opportunity for other research groups to adapt their numerical approaches to the observed Ruhr sandstone's microfabric and incorporate possible reduced permeabilities.…”
Section: The Capabilities Of the Geological Driven Workflowmentioning
confidence: 99%
“…The data sets will be available in the Data Repository of the University of Stuttgart (DaRUS). Two data sets are separately published: images of optical microscopy together with the log data, including flow rates and pressure measurements, can be found in Weinhardt et al (2021). The XRCT data set is published in Vahid .…”
Section: Data Availability Statementmentioning
confidence: 99%